From a labyrinthine fetal sarcophagus exercises of manganellian topo-analysis - Crivella, Giuseppe (Scenari, 2021)
This text focuses on some aspects of Giorgio Manganelli’s narrative production examined from an interpretation perspective that places the theme of spatiality at the center of attention. Through a series of cross-references to the studies of Bachelard, Genette and Matoré, our analyzes will try to show the way in which the Milanese writer works fictional space in his texts. We thus come to highlight some principles of topopoetics which we then compare with some theses developed by Jean-Jacques Wunenburger in an essay of 2017. In this way, re-reading texts such as La riga bianca, Nuovo Commento, Sconclusione through this critical scheme, we can propose a small Manganellian topo-analysis treatise. Here Abbot’s «miniaturistic Platonism» coexists with a rich sample of figures and topological structures, where the dysphoric dimension in which they take shape and form always ends up transforming itself into a formidable reflection on the possibilities of literature.